(untitled) (Applied Biological Research, 2018)
This study was aimed to evaluate the quality of doughnuts made from pearl millet-wheat-whey protein isolate composite blend. Flour blends of pearl millet and refined wheat flour (RWF) were composite at replacement levels of 10, 20, 30 and 40% with 10% whey protein isolates in each treatment. The nutrient contents of flour blends were determined using standard methods. The products were analyzed for their proximate composition and sensory attributes. The protein content of blends decreased steadily with increasing content of pearl millet flour (PMF) (17.99% in 00:90:10::PMF:RWF:WPI to 14.44% in 40:50:10:: PMF:RWF:WPI) while crude fibre content increased. The highest moisture content of 15.43%, crude fat 24.76%, crude fibre 2.36% and ash content of 2.81% were observed in 40:50:10::PMF: RWF: WPI treatment. However, the treatment 00:90:10::PMF:RWF:WPI yielded highest value of crude protein. On the basis of sensory evaluation, treatment 00:100:00::PMF:RWF:WPI recorded highest score for colour (8.96), texture (8.74), taste (8.87) and overall acceptability (8.87) in doughnuts; whereas reatment 40:50:10::PMF:RWF: WPI recorded lowest score for sensory parameters. In general, incorporation of refined wheat flour and whey protein isolates with pearl millet flour for doughnuts upto 20% level were acceptable.